FEATURES OF USING A COMPLEX HEATING SYSTEM WITH PHASE-TRANSITIONAL THERMAL ACCUMULATOR DURING THE PRE-START AND AFTER-START VEHICLE ENGINE HEATING UNDER ITS - Volkov, V.; Grytsuk, I.; Волков, В. П.; Грицук, І. В.; Волков, В. П.; Грицук, И. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article deals with the features of applying a vehicular engine complex heating system with a phase-transitional thermal accumulator. The article describes the structure of information package for studying the internal combustion engine of the vehicle equipped with a complex heating system and thermal accumulator during the pre-start and after-start heating.
ОСОБЛИВОСТІ ЗАСТОСУВАННЯ КОМПЛЕКСНОЇ СИСТЕМИ ПРОГРІВУ З ТЕПЛОВИМ АКУМУЛЯТОРОМ ФАЗОВОГО ПЕРЕХОДУ В ПРОЦЕСАХ ПЕРЕДПУСКОВОГО І ПІСЛЯПУСКОВОГО ПРОГРІВУ АВТОМОБІЛЬНОГО ДВИГУНА В УМОВАХ ITS
ОСОБЕННОСТИ ПРИМЕНЕНИЯ КОМПЛЕКСНОЙ СИСТЕМЫ ПРОГРЕВА С ТЕПЛОВЫМ АККУМУЛЯТОРОМ ФАЗОВОГО ПЕРЕХОДА В ПРОЦЕССАХ ПРЕДПУСКОВОГО И ПОСЛЕПУСКОВОГО ПРОГРЕВА АВТОМОБИЛЬНОГО ДВИГАТЕЛЯ В УСЛОВИЯХ ITS
Keywords: complex heating; vehicular engine; pre-start and after-start heating; heating processes; vehicle; measuring complex; specifications; комплексний прогрів; транспортний двигун; передпусковий і післяпусковий прогрів; режими прогріву; транспортний засіб; комплексный прогрев; транспортный двигатель; предпусковой и послепусковой прогрев; режимы прогрева; транспортное средство; 621.43+621.43.016.4-57+536.421+541.6:541.183